2018
DOI: 10.3389/fmicb.2018.00790
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Oxide Nanoparticles: Effective Agricultural Antibacterial Agent Against Ralstonia solanacearum

Abstract: Magnesium (Mg) is an essential mineral element for plants and is nontoxic to organisms. In this study, we took advantage of nanotechnologies to systematically investigate the antibacterial mechanisms of magnesium oxide nanoparticles (MgONPs) against the phytopathogen Ralstonia solanacearum (R. solanacearum) in vitro and in vivo for the first time. R. solanacearum has contributed to catastrophic bacterial wilt, which has resulted in the world-wide reduction of tobacco production. The results demonstrated that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
187
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 262 publications
(205 citation statements)
references
References 80 publications
15
187
0
3
Order By: Relevance
“…The electrostatic interaction might mediate the excellent nanoparticle-cell aggregates, which can be observed in previous reports regarding the antibacterial activities of a series of nanoparticles (Chen et al, 2016a,b;Pan et al, 2013). Indeed, our previous studies have found that nMgO and graphene were visibly directly attached to phytopathogens, affecting energy metabolism and cell membrane potential (Cai et al, 2018a). Ideally, adsorption of nMgO on fungal cells could disturb membrane potential as a result of enhanced adherence.…”
Section: Destabilization Of Fungal Cell Membranementioning
confidence: 63%
See 4 more Smart Citations
“…The electrostatic interaction might mediate the excellent nanoparticle-cell aggregates, which can be observed in previous reports regarding the antibacterial activities of a series of nanoparticles (Chen et al, 2016a,b;Pan et al, 2013). Indeed, our previous studies have found that nMgO and graphene were visibly directly attached to phytopathogens, affecting energy metabolism and cell membrane potential (Cai et al, 2018a). Ideally, adsorption of nMgO on fungal cells could disturb membrane potential as a result of enhanced adherence.…”
Section: Destabilization Of Fungal Cell Membranementioning
confidence: 63%
“…Enhanced adherence to pathogens of antifungal drugs was caused by decreased electric repulsive forces (Miyake et al, 1990). Consequently, nanoparticles could be capable of physically damaging the cell envelope, which was confirmed by SEM and TEM imaging above (Sharma et al, 2015;Cai et al, 2018a).…”
Section: Destabilization Of Fungal Cell Membranementioning
confidence: 76%
See 3 more Smart Citations